2016
DOI: 10.1242/dmm.024521
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between afferent rearrangements and behavioral deficits after local excitotoxic insult in the mammalian vestibule: an animal model of vertigo symptoms?

Abstract: Damage to inner ear afferent terminals is believed to result in many auditory and vestibular dysfunctions. The sequence of afferent injuries and repair, as well as their correlation with vertigo symptoms, remains poorly documented. In particular, information on the changes that take place at the primary vestibular endings during the first hours following a selective insult is lacking. In the present study, we combined histological analysis with behavioral assessments of vestibular function in a rat model of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 72 publications
(107 reference statements)
3
30
0
2
Order By: Relevance
“…In parallel with the quantitative analysis indicated above, we evaluated qualitatively the vestibular syndrome following UVN using a method recently validated [ 6 ]. The vestibular syndrome evoked in the rat after UVN is composed of typical symptoms previously reported in other vestibular disorder models, such as the cat UVN model [ 8 ], the rodent models of unilateral excitotoxically-induced transient vestibular deafferentation [ 9 , 10 , 11 ] or unilateral chemical labyrintectomy [ 12 ]. These symptoms, which include tumbling, retropulsion, circling, bobbing and head tilt, are together present in the acute phase and sequentially disappear following specific time courses.…”
Section: Methodsmentioning
confidence: 99%
“…In parallel with the quantitative analysis indicated above, we evaluated qualitatively the vestibular syndrome following UVN using a method recently validated [ 6 ]. The vestibular syndrome evoked in the rat after UVN is composed of typical symptoms previously reported in other vestibular disorder models, such as the cat UVN model [ 8 ], the rodent models of unilateral excitotoxically-induced transient vestibular deafferentation [ 9 , 10 , 11 ] or unilateral chemical labyrintectomy [ 12 ]. These symptoms, which include tumbling, retropulsion, circling, bobbing and head tilt, are together present in the acute phase and sequentially disappear following specific time courses.…”
Section: Methodsmentioning
confidence: 99%
“…The researchers set out either, on the basis of an epidemiological rationale, the pathogenic conditions likely to induce vestibular dysfunction and its functional consequences, or the neurophysiological mechanisms likely involved. The first case included: 1) ototoxic-based vestibular damages, reproducing inner ear-specific toxicity of drugs such as aminoglycosides or cisplatin, and food-born ototoxicity (Zhang et al 2003;Hirvonen et al 2005;Xia, Chen, and Yin 2012;Vignaux et al 2012); 2) excitotoxically-induced vestibular damages, reproducing the deleterious consequences on the first synapse of sensory cells suffering (O'Neill et al 1999;Brugeaud et al 2007;Desmadryl et al 2012;Dyhrfjeld-Johnsen et al 2013;Gaboyard-Niay et al 2016); 3) destruction of peripheral receptors through surgical labyrintectomy (Smith and Curthoys 1989;Patk et al 2003;Hitier et al 2010); 4) vestibular neurectomy that relates to the full section of the vestibular nerve. This operation can be achieved either by severing the vestibular nerve peripherally (between the vestibular endorgans and the Scarpa's ganglion) (Li, Godfrey, and Rubin 1995;Hamann et al 1998)or centrally (between the Scarpa's ganglion and the brainstem).…”
Section: Animal Models Of Vestibular Pathologiesmentioning
confidence: 99%
“…With the aim to reproduce these excitotoxic damages, we developed in rodents a method of transtympanic administration of glutamate receptors agonists ( 26 ). By combining electron microscopy and immunohistochemical approaches, we confirmed that the local excitotoxic environment generated by the strong afflux of glutamate-receptors agonist evoked selective destruction of the synaptic contacts between vestibular hair cells and primary neurons forming the vestibular nerve ( 26 , 27 ). Swellings and retractions of the postsynaptic terminals were interpreted as the consequence of the massive influx of cations and water through the AMPA-kainate receptors.…”
Section: Discussionmentioning
confidence: 61%
“…This model allowed us to identify the time course of the different postural-locomotor symptoms that compose AVS. It also highlighted the ability of rodents to quickly restore their balance and posture, based on a robust propensity of peripheral vestibular synapses to spontaneously repair following kainate-induced deafferentation ( 27 ). A recent adaptation of the mouse TTK model and the development of more precise monitoring of both the specific signs of vestibular function and the general behavioral alterations provided the opportunity to better follow the temporal evolution of several specific symptoms of AVS, while better appreciating the different phases that compose this syndrome ( 28 ).…”
Section: Introductionmentioning
confidence: 99%